Kinerja Penyuluh Pertanian dan Dampaknya pada Kompetensi Petani Kakao di Empat Wilayah Sulawesi Selatan - Sapar Sapar; Amri Jahi; Amiruddin Saleh; I.G Putu Purnaba (Jurnal Penyuluhan, 2012)
The agricultural extension worker’s performance is the work outputs achieved by agricultural extension workers in conducting their jobs. The aim of this research is to know the factors which influence to the agricultural extension worker’s performance and the connection between the factors. Also, to know that factors influences the cacao farmers competence. The population of this research is all the agricultural extension workers in four district, South Sulawesi province (447 person). The sample of this research referred to Slovin method from among 106 (one hundred six) agricultural extension workers, 106 (one hundred six) group farmers leaders and 212 (two hundred twelve) cacao farmers . The design of this research was conducted by surveying and interviewing. LISREL program with ‘SEM’ was used in analyzing data. The Result of this research show that the agricultural extension worker’s performance was influenced significantly by characteristic, competence, motivation and self reliance. The total influence of them were 10 percent and 90 percent were represent other influences outside this study. The suggestion was that their performance must be improved by providing special training to improve their capability in agricultural extension planning, monitoring and evaluation, agricultural extension development and technology disemination.Key words: Performance, competencies, motivation